Modernizing Land Ownership Systems through LandLedger+: Ensuring Reliability, Accessibility, and Fraud Prevention - Raut, Renuka; Binoy, Mathew; Raju, Emil Treesa; Daby, Denil (International Journal of Recent Advances in Engineering and Technology, 2025)
In India, land ownership still largely depends on paper- based documentation, which is susceptible to deterioration, forgery, and administrative inefficiencies. This research introduces LandLedger+, a secure and transparent digital land registry system designed to modernize property record management through cryptographic protection, cloud integration, and user-friendly accessibility. A systematic, phased methodology was employed to ensure structured development and reliable implementation. The process began with requirement analysis and research to identify user needs, functional requirements, and appropriate cryptographic algorithms. The finalized technology stack comprised Python, Django, Firebase/Supabase, and Progressive Web App (PWA) frameworks. The frontend was developed using HTML5, CSS/Tailwind, and JavaScript (React optional) to create responsive, cross-platform interfaces, while the backend managed authentication, document handling, and real-time data synchronization. Cryptographic algorithms were implemented for secure file encryption and decryption, complemented by role- based access control and metadata-based search. Rigorous testing and debugging ensured system security, performance, and functionality, followed by documentation and deployment on Vercel and Netlify. The results demonstrated that LandLedger+ effectively prevented duplication and unauthorized alterations, ensured data immutability through hashing, and enhanced accessibility through a user-friendly web interface. The discussion highlights the system’s potential to reduce fraud, improve administrative efficiency, and enable transparent property transfers. In conclusion, LandLedger+ presents a scalable and secure framework for transforming India’s land registry system, combining cryptographic security with cloud- based architecture to promote transparency, reduce fraud, and establish a citizen-centric approach to land governance.